Daya Gabung Galur Jagung pada Cekaman Nitrogen Rendah - Aulianta, Ladikta Hubah; Santoso, Juli; Makhziah, Makhziah; Mejaya, I Made Jana (Agrotechnology Research Journal, 2022)
Reduction of nitrogen in the soil is a problem in corn cultivation that can cause decrease production. The efforts to prevent this problem is to assemble superior maize that is low nitrogen resistance and high production by crossing different corn elders. This study was to analyse the combining ability of five lines (G1, G2, G3, G4 and G5) under normal and low nitrogen conditions used a half diallel cross design using the Griffing’s model I method formula to analyse 10 genotypes. The research design used a split plot design (SPD) with 3 replications, the research location was in the experimental garden of Center for Agricultural Research and Technology in Kebondalem, Mojosari, Mojokerto East Java. The value of the general combining ability (GCA) of the G3 elders significantly affected the weight parameters of the cobs under low nitrogen conditions. The results of the specific combining ability (DGK) on the G7 and G8 crosses had high SCA values on the yield character and weight of 100 seeds under normal conditions and nitrogen stress. Genotype G6 has a high SCA value for cob weight characters.